Уровни специфичности географической изменчивости признаков черепа млекопитающих - Россолимо, О.Л.; Павлинов, И.Я. (Вестник зоологии, 1978)
Coordination of geographic variability of skull characters was studied in six species of mammals by means of the correlation analysis. Three specificity levels of geographic variability are distinguished: I — the highest level determined by insignificant values of the coefficient Rg; II — the middle level determined by significant values of the coefficient Rg<+0.90=+0.95; III — the lowest level determined by values of Rg>+0.90=+0.95. Regularities of geographic correlation of characters are species specific. Similarity of species as to the structure of the specificity levels of geographic variability of characters is determined mainly by similarity in manifestation of ecogeographic corrdination.